Model Bisnis Produk Pupukin! (Eco-Friendly Slow Release Fertlizer 3-in-1) dengan Pendekatan Lean Canvas - Prili Alisha; Dira Purwasih; Rizqia Nadira Ronaldo; Stanislaus Adhi Pramudya; Muhammad Yasyfa Kusumadinata; Eddy Renaldi; Vira Kusuma Dewi (Universitas Galuh, 2026)
Pupukin! is an innovative eco-friendly fertilizer developed as a practical solution for urban farming activities. This study aims to describe the business performance and to map the business model of Pupukin! using the Lean Canvas approach. A case study method was employed, with data analyzed based on the nine elements of the Lean Canvas. The results show that Pupukin! adopts a slow-release fertilizer concept using banana pseudostem base and the waste of shrimp shell as row materials, formulated as a multifunctional fertilizer capable of supplying plant nutrients, stimulating growth, and protecting plants from pests and diseases for up to 90 days with a single application. Pupukin!’s business activities cover pre-production, production, and post-production stages, supported by laboratory research, limited field trials, and initial-scale marketing. Pricing is determined based on production costs and the purchasing power of urban consumers, with marketing strategis that utilize social media, online marketplaces, and direct selling. The Lean Canvas mapping indicates that Pupukin! targets urban and peri-urban consumers with environmentally friendly lifestyles and limited time for plant maintenance. Marketing activities are supported by online and offline distribution channles, with the main revenue streams derived from direct product sales and sales through partners, while the cost structure remains manageable with an initial capital of IDR 10,100,000. Market validation through sales performance, repeat purchases, and cosumer feedback demonstrates that Pupukin! is well accepted by the target market. Therefore, Pupukin! has the potential to be further developed as an innovative agribusiness vemture that is relevant and sustainable for the advance of urban farming.